Reversible Perfusion Changes during Acute Attacks in Glucose Transporter Type 1 Deficiency Syndrome: A Pediatric Case Series - Pacchiano, Francesco; Doneda, Chiara; Arrigoni, Filippo; Tortora, Mario; Contaldo, Maria Teresa; Lomonaco, Germana; Previtali, Roberto; Olivotto, Sara; Veggiotti, Pierangelo; Parazzini, Cecilia; Righini, Andrea (American Journal of Neuroradiology, 2025)
SUMMARY: Glucose transporter type 1 deficiency syndrome (GLUT1-DS) is an uncommon condition represented by an infantile-onset disorder, frequently arising from heterozygous mutations in the SLC2A1 gene. Individuals with GLUT1-DS may present with early-onset seizures (typically manifesting before 4 years of age), developmental delay, and complex movement disorders. In fewer cases, stroke-like events or hemiplegic migraine-like symptoms are also reported, defined by unilateral paresis affecting 1 side of the body and/or one-half of the face, occasionally accompanied by speech impairment. Currently, the pathomechanism underlying these acute transient clinical manifestations is poorly understood. MR imaging studies performed in the absence of acute manifestations frequently reveal nonspecific imaging signs associated with this syndrome. We present findings obtained using the arterial spin-labeling technique for perfusion imaging and MRA during the acute onset of stroke-like episodes in a series of 4 pediatric patients with GLUT1-DS. We observed reversible hypoperfusion in the left hemisphere and associated reversible attenuation of distal MCA branches on MRA. A notable association between unilateral cerebral hypoperfusion and transient crossed cerebellar diaschisis was evident on perfusion maps as well.ASLarterial spin-labelingEEGelectroencephalographyGLUT1glucose transporter 1GLUT1-DSglucose transporter type 1 deficiency syndromepCASLpseudocontinuous arterial spin-labeling